Tradable permits in logging operations - M. Dragoi (Journal of Forest Science, 2002)
The paper presents a new system of tradable permits combined with ecological bonds that is able to promote environment-friendly logging technologies, supposed to be less harmful to the forest ecosystem. All loggers deposit in advance ecological bonds on to-be-harvested volume basis and a certain number of permits to damage is freely given per each cubic meter, by the public authority. After surveying the damage caused throughout all harvested tracts, the number of permits on the volume basis is recomputed for each logger according to the magnitude and importance of damage caused. The logging company that caused smallest damage and saved most permits is allowed to sell to another competitor the number of permits which makes the difference between the two companies. The main section of the paper presents five simulations based on reliable scenarios that have been developed on some effective data referring to two types of damage produced by seven Romanian logging companies in 1999, in Suceava state county forest. Firstly, the deterministic scenario shows that environment-friendly companies become more competitive due to the new system because they have an additional income from sold permits. Conversely, companies unable to protect the environment are to pay more for being in business and thus their capacity to buy more timber is diminished. Assuming that companies able to get money due to this kind of trade are also able to improve their technology and can afford to buy more timber, it was demonstrated that the technological transfer is encouraged by the new system that might be combined with a regular compensation paid to the landowner as well. The greater the bond, the more advantageous the system for fewer and fewer companies. The lower the bond, the more companies can take advantage of the system but less money is collected from a given market.